University freshmen's excessive smartphone use and psychological safety during the COVID-19 pandemic - Yang, Qingsong; Shi, Mengxi; Zeng, Lianping; Xu, Ping (Frontiers in Psychiatry, 2022)
Although the relationship between excessive smartphone use and mental health during COVID-19 pandemic has been confirmed, the affecting mechanism in this relationship is little known. The study aims to identify the impact of excessive smartphone use on mental health and its mechanisms among college freshmen. In this study, 1224 college freshmen were randomly selected from several universities in Guizhou, China. Psychological Safety Scale was used to evaluate mental health of college freshmen; Mobile Phone Dependence Scale was used to evaluate excessive smartphone use; Hardiness Questionnaire was used to evaluate hardiness; and Interpersonal Relation Synthetic Diagnose Test was used to evaluate interpersonal distress. The findings showed that: (1) the greater the degree of excessive smartphone use, the more serious interpersonal distress and the lower hardiness and psychological safety of college freshmen; (2) the excessive smartphone use not only directly affected psychological safety of college freshmen, but also indirectly affected psychological safety through the independent mediation of hardiness and interpersonal distress, and the chain mediation of hardiness and interpersonal distress. In general, the excessive smartphone use in college freshmen could lead to a decline in psychological safety, and hardiness and interpersonal distress plays a complex role in the relationship. During the pandemic, the intervention on the mental health of college freshmen should not only guide them to use smartphone reasonably, but also provide support and guidance for the enhancement of hardiness and improvement of interpersonal relationships.